Legitimacy signals and family IPO performances - Ding, Hung-bin; Pukthuanthong, Kuntara (Journal of Business Economics and Management, 2013)
The objective of this research is to examine the relationship between signals including governance and management practices and the performance of family firms IPOs. Using IPO data of 129 family firms and 129 comparable non-family firms from the Taiwan Stock Exchange, our findings highlighted the role of non-family insiders, or non-family affiliated directors in the IPOs of family firms. Our comparison between family and non-family IPOs shows hiring prestigious underwriters significantly improves the performance of family firm IPOs. Finally, we found the industries of IPO firms moderate the relationship between corporate governance characteristics and IPO performances, as non-family firms in technology industries are perceived to be more legitimate than their family counterparts. This paper makes three contributions to existing research. Firstly, we contribute to the legitimacy theory by suggesting an interaction effect between internal (organizational) and external (environmental) factors. Secondly, our analysis highlighted the roles of affiliated directors and industry in the performances of public family firms. Thirdly, this study contributes to the family business research by underscoring the differences between family and non-family firms in the IPO context.